Vitamin E prevents ethylene bis(dithiocarbamate) pesticide zineb-induced sister chromatid exchange in Chinese hamster ovary cells - Soloneski, Sonia María Elsa (2003)
The in vitro effect of the antioxidant α-tocopherol, vitamin E, on deleterious effects induced by the dithiocarbamate fungicide zineb and its commercial formulation azzurro on Chinese hamster ovary (CHO) cells was studied by using frequency of sister chromatid exchanges (SCEs), cell cycle progression and mitotic index (MI) as genetic end points. Both zineb and azzurro activities were tested within the range 0.1-100.0 μg/ml on exponentially growing CHO cells preincubated for 24 h in the presence or absence of 50.0 μg/ml vitamin E. SCE frequencies increased significantly over control values in a concentration-dependent manner in zineb- and azzurro-treated cultures at concentrations of 0.1-10.0 and 0.1-25.0 μg/ml, respectively. When target cells were preincubated with vitamin E, the number of SCEs was significantly lower than that observed in cells exposed only to 1.0-10.0 μg/ml zineb or 1.0-25.0 μg/ml azzurro, but higher than control values. Cytotoxicity was observed at concentrations higher than 25.0 and 50.0 μg/ml zineb and azzurro, respectively, regardless of the absence or presence of vitamin E. Regression analysis showed that the proliferative rate index decreased as a function of the concentration of zineb (0.1-10.0 μg/ml concentration range) and azzurro (0.1-25.0 μg/ml concentration range) titrated into cultures. For both chemicals, progressive concentration-related inhibition of the mitotic activity from cultures was observed when 10.0 μg/ml zineb or 1.0-25.0 μg/ml azzurro was employed. However, no significant alteration in cell cycle progression or MI was observed between vitamin E-preincubated cultures and those treated only with zineb and azzurro.